A Method of Making DEM by Data Fusion of Multi-Device Point Cloud. Issue 7 (1st November 2022) - Song, Dianwei; Li, Shenghan; Li, Silin; Jin, Shuaishuai; Tang, Dongdong; Tan, Yi
Abstract: When planning to build greenways in jungles, accurate topographic information of the target area is significant. The traditional topographic survey is usually manually conducted with several tools, which is not only labour-intensive and time-consuming, but also has limitations in accuracy and efficiency. Therefore, this paper presents a method to generate a digital elevation model based on unmanned aerial vehicle (UAV) and ground equipment supplements the ground area covered by vegetation where UAV-based equipment cannot reach. Iterated Closest Point (ICP) is first used to register the point cloud data from UAV and ground mobile equipment. Then, point cloud classification is used to non-ground point cloud. Finally, the digital elevation model and contour line are obtained. A real experiment is conducted to validate the presented method. The results show that this method not only overcomes the UAV's limitation of having difficulty in collecting point cloud data from the covered area, but also realizes large-area point cloud data collection that ground mobile equipment cannot. Compared with the traditional base station and multi-person assistance measurement, the presented method is more efficient and effective.